Carnosic acid attenuates doxorubicin-induced cardiotoxicity by decreasing oxidative stress and its concomitant pathological consequences. (August 2022) - Manna, Prasenjit; Dewanjee, Saikat; Joardar, Swarnalata; Chakraborty, Pratik; Bhattacharya, Hiranmoy; Bhanja, Shrestha; Bhattacharyya, Chiranjib; Bhowmik, Manas; Bhowmick, Shovonlal; Saha, Achintya; Das, Joydeep; Sil, Parames C.
Abstract: This work aimed to reveal the protective mechanism of CA against Dox (doxorubicin)-induced cardiotoxicity. In isolated murine cardiomyocytes, CA showed a concentration-dependent cytoprotective effect against Dox. Dox treatment significantly (p < 0.01) increased the formation of reactive oxygen species (ROS), increased NO levels, activated NADPH oxidase, and inactivated the cellular redox defense mechanism in cardiac cells, resulting in augmented oxidative stress in cardiomyocytes and rat hearts. Dox-induced oxidative stress significantly (p < 0.01) upregulated several pathogenic signal transductions, which induced apoptosis, inflammation, and fibrosis in cardiomyocytes and murine hearts. In contrast, CA significantly (p < 0.05–0.01) reciprocated Dox-induced cardiac apoptosis, inflammation, and fibrosis by suppressing oxidative stress and interfering with pathological signaling events in both isolated murine cardiomyocytes and rat hearts. CA treatment significantly (p < 0.05–0.01) countered Dox-mediated pathological changes in blood parameters in rats. Histological examinations backed up the pharmacological findings. In silico chemometric investigations predicted potential interactions between CA and studied signal proteins, as well as the drug-like features of CA. Thus, it would be concluded that CA has the potential to be regarded as an effective agent to alleviate Dox-mediated cardiotoxicity in the future. Graphical abstract: Image 1